Fresno County Bar Association with Carol Herbert, Dean San Joaquin College of Law - Watkins, Howard::::::::: (1983)
Fresno County Bar Association President-Elect Rodney Worrel, Dean Carol Herbert laughing, Tomar Mason, Judge John "Nip" Gallagher